Improving safety in high workload environment - Almghairbi, Dalal (2018)
Background: Recent advances in medical technology, primarily in the anaesthetic and operating rooms, has influenced a change of workload from being just a physical dimensional element to a mental dimensional component also. Evaluations of anaesthesia workload dimensions have become a necessity due to the ever-changing and complexity of such workplace environments, and most essentially, the need for patient safety.